Group analysis, nonlinear self-adjointness, conservation laws, and soliton solutions for the mKdV systems - Wang, Gangwei; Kara, Abdul H. H.; Vega-Guzman, Jose; Biswas, Anjan (Nonlinear Analysis: Modelling and Control, 2017)
We study the symmetry groups, conservation laws, solitons, and singular solitary waves of some versions of systems of the modified KdV equations.